Teachers’ ICT skills and application of ICT in the middle and higher secondary schools in Bhutan - Nidup, Yeshi (Journal of ICT in Education, 2022)
This study explored teachers’ ICT skills and application of ICT in education in eight middle and higher secondary schools in Bhutan. A quantitative method was applied and convenience sampling was used to collect data from 37 teachers from eight middle and higher secondary schools through survey questionnaires developed using a five-point Likert scale. The first set of questionnaires asked about teachers’ ICT skills and knowledge, and the second set asked about the application of ICT in education. The data was analyzed using an excel data analysis tool package in simple descriptive form interpreted in percent, means, and standard deviation. The findings showed that teachers possess basic ICT skills and knowledge which are necessary for them. It was found that teachers are using ICT in their daily teaching and learning but only for basic purposes since many lack ICT skills at the advanced level. There were only a few teachers who used ICT for a variety of purposes at the advanced levels to enhance teaching and learning. They were some teachers who have never or rarely used ICT in teaching. This is something that led the researchers to deeply ponder and opened a room to plan for another research to find out why they have never or rarely used ICT in teaching.